Ocular complications in inflamatory bowel disease - Ülkü DAĞLI; Yıldız ÖZDEMİR and Aysel ÜLKER and Hülya ÖVER and Azmi SERİN and Gülcan KURAL and Leziz ONARAN (Turkish Journal of Gastroenterology, 2019)
-